OS 03-04 INFLUENCE OF FAMILY AND PEER NETWORKS ON SALT REDUCTION IN CHILDREN IN THE SCHOOL-EDUSALT (SCHOOL BASED EDUCATION PROGRAMME TO REDUCE SALT) TRIAL. (September 2016) - Ma, Yuan; Feng, Xiangxian; Zhang, Jing; Wang, Haijun; Yuan, Jianhui; Li, Zhifang; Han, Yanbo; Zhang, Jianbin; He, Feng J; MacGregor, Graham; Wu, Yangfeng
Abstract : Objective: To identify the social determinants shaping children's behaviour on salt reduction from a network perspective. Design and method: School-EduSalt is a cluster-randomized controlled trial carried out in 28 primary schools in northern China involving 279 families (279 children aged 10.1 ± 0.5yrs and 553 adults). A 3.5-month education on salt reduction was delivered to the 14 schools (classes) in the intervention group, of which children and their families achieved a significant reduction in salt intake as measured by 24-hour urine sodium. Information on ego-centric family networks was collected for the 279 children while an additional post-trial survey was conducted for all the children in the 28 recruited classes (n = 1273) to obtain information on children's peer networks and behaviour change. Mixed models and exponential random graph (ERG) models was used in network analysis. Network was visualized using NetDraw. Results: The reduction of salt intake in children closely correlated with that of their adult family members (r = 0.4, P < 0.001). Children whose father held a supportive attitude had a 0.9 g/d greater reduction in salt intake (P = 0.04), as were children whose families attended more frequently (P = 0.02) in the intervention activities after adjusting for age, sex, BMI and baseline salt intake. Moreover, children who were embedded in a network with larger density (i.e. better interconnected) and those who had a greater degree centrality (i.e. more "popular") had significantly higher score on salt reduction with adjustment of age, sex and class size (P = 0.048 and P = 0.03, respectively). Conclusions: Both family and peer networks significantly influence children's behaviour on salt reduction from multiple different aspects. Our study is the first to have explored the effect of social network on behaviour of salt reduction and demonstrated the importance of targeting the macro networks individuals embedded in. Our study offers novel insight into the social determinants of behaviour change and provides evidence to optimize future salt-reduction strategies.